2018
DOI: 10.1590/fst.15417
|View full text |Cite
|
Sign up to set email alerts
|

Buriti of the cerrado of Minas Gerais, Brazil: physical and chemical characterization and content of carotenoids and vitamins

Abstract: The fruit species of the Brazilian Cerrado, such as buriti (Mauritia vinifera), occupy a prominent position in the ecosystem since they contribute to the economic potential of the region and have high nutritional value. We aimed to evaluate the physical characteristics, chemical composition and content of vitamin C, carotenoids, vitamin E and folates in pulp of buriti from the Brazilian Cerrado of Minas Gerais, Brazil. The length, diameter, mass and fruit yield were evaluated. The titratable acidity was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
0
5
0
2
Order By: Relevance
“…The whole fruit had a mass of 10.07 g ( Table 1 ). The buritirana fruit showed a lower mass in comparison with buriti ( Mauritia vinífera ) [ 29 ], which presented a WS fraction of 60.43 g, PU of 13.55 g, PE of 15.68 g and SE of 31.19 g. Moreover, the buritirana seed ( Table 1 ) presented the highest mass, followed by the peel and pulp (6.46 g > 1.94 g > 1.67 g), representing 64.15%, 19.27% and 16.58% of the fruit, respectively. These values were higher than those of buriti pulp ( Mauritia flexuosa ) grown in Goiás and Pará (16.43% and 8.53%, respectively) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The whole fruit had a mass of 10.07 g ( Table 1 ). The buritirana fruit showed a lower mass in comparison with buriti ( Mauritia vinífera ) [ 29 ], which presented a WS fraction of 60.43 g, PU of 13.55 g, PE of 15.68 g and SE of 31.19 g. Moreover, the buritirana seed ( Table 1 ) presented the highest mass, followed by the peel and pulp (6.46 g > 1.94 g > 1.67 g), representing 64.15%, 19.27% and 16.58% of the fruit, respectively. These values were higher than those of buriti pulp ( Mauritia flexuosa ) grown in Goiás and Pará (16.43% and 8.53%, respectively) [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Differently, Martínez‐Cervera et al (2011) observed higher lightness of crust and crumb (38.30 to 39.60) in chocolate muffins, in addition to redness (5.90–6.50) and yellowness (5.60–6.00) slightly lower than the results of the present study. The discrepancies in color coordinates may be occurred due to the lower proportion of cocoa and wheat flour in the study by Martínez‐Cervera et al (2011), in addition to the lack of PDBB, which is brown with red and orange nuances resulting from the high carotenoid content in buriti fruit (Hamacek et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Manhães and Sabaa-Srur (2011) detected a high content of iron, copper, chromium, magnesium, selenium, and iodine in the fruit pulp. Other studies found the presence of pectin, α-and β-carotenes, vitamin C, tocotrienols, tocopherols, folates, and phenolic compounds (Hamacek et al, 2018;Leite et al, 2021;Schiassi et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…A viabilidade celular foi determinada por ensaio de redução de MTT (adaptado de MOSMANN, 1983 SANDRI et al, 2017;HAMACEK et al, 2018;SCHIASSI et al, 2018;BERNI et al, 2019;NASCIMENTO-SILVA et al, 2020). Os teores de lipídeos e carboidratos mostraram-se na faixa descrita pelos demais estudos oscilando, respectivamente, entre 6,20 e 22,20; e 2,10 a 26,20 g / 100g, respectivamente.…”
Section: Viabilidade Celularunclassified
“…Os teores de carotenoides totais e -caroteno da polpa de buriti foram, respectivamente, 370,00 µg / g e 305,00 µg / g. Estes teores de carotenoides totais e de -caroteno encontraram-se dentro da faixa de valores descritos na literatura (233,60 µg / g a 589,00 µg / g e 137,10 µg / g a 372,30 µg / g, respectivamente) para amostras de buriti de diferentes regiões (DE ROSSO & MERCADANTE, 2007;RODRIGUEZ-AMAYA;AMAYA-FARFAN, 2008;MANHÃES & SABAA-SRUR, 2011;CÂNDIDO et al, 2015;SANTOS et al, 2015;ROMERO et al, 2015, HAMACEK et al, 2018PEREIRA-FREIRE et al, 2018).…”
Section: Determinação De Carotenoidesunclassified